2015
DOI: 10.1007/s13197-015-1896-y
|View full text |Cite
|
Sign up to set email alerts
|

Sonication inhibited browning but decreased polyphenols contents and antioxidant activity of fresh apple (malus pumila mill, cv. Red Fuji) juice

Abstract: Enzyme browning is the main challenge in the preparation of fresh apple juice. The influence of sonication on browning, as well as polyphenols and antioxidant activity of fresh apple juice was investigated. It was found that ultrasound can inhibit the browning of fresh apple (Malus pumila Mill, cv. Red Fuji) juice, but decreased the contents of total phenolic content (TPC), total flavonoid content (TFC) and chlorogenic acid and reduced the antioxidant activity. On the whole, ultrasound technology cannot be use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
24
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 26 publications
5
24
0
1
Order By: Relevance
“…Ultrasound with nisin‐treated samples showed a significantly higher ( p < .05) browning index initially as well as during storage (Table ). Similar results were reported by Sun et al () for ultrasound‐treated apple juice, which showed a higher browning index than untreated apple juice. Fonteles et al () found a significant reduction of POD and PPO activities with an ultrasound power intensity of 376 W/cm 2 for 10 min at 4°C.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Ultrasound with nisin‐treated samples showed a significantly higher ( p < .05) browning index initially as well as during storage (Table ). Similar results were reported by Sun et al () for ultrasound‐treated apple juice, which showed a higher browning index than untreated apple juice. Fonteles et al () found a significant reduction of POD and PPO activities with an ultrasound power intensity of 376 W/cm 2 for 10 min at 4°C.…”
Section: Resultssupporting
confidence: 90%
“…The higher losses in ascorbic acid (62.58%), total sugars (31.81%), phenolic content (44.27%), and flavonoids (48.04%) were observed probably due to the production of free radicals that may degrade polyphenols, flavonoids, ascorbic acids, and sugars by oxidizing them. Sun, Zhong, Cao, Lin, and Ye () also reported a decrease in the phenolic content, flavonoid content, and antioxidant activity in ultrasound‐treated apple juice. The ascorbic acid content of TCW was reduced to 0.69 mg/100 ml (53% loss), phenolic content to 2.12 mg/100 ml (43.5% loss), and flavonoids to 1.45 µg eq of catechin/ml (48% loss) by heat treatment at 85°C for 10 min.…”
Section: Resultsmentioning
confidence: 90%
“…From the results, it was seen a decrease in AA of liposomes formed by ultrasonication and microfluidization compared to 0.1% green tea extract solution. Similar results were observed by a previous study of Sun and others () demonstrating a decrease in AA of fresh apple due to the synergic effect of the ultrasound and temperature increase. Moreover, a decrease in AA due to microfluidization could be explained by overheating of the sample during microfluidization.…”
Section: Resultssupporting
confidence: 92%
“…Upon the addition of GS to AP, the main anthocyanins of red GS, namely the 3-O-glucosides of five common anthocyanidins: cyanidin, peonidin, petunidin, delphinidin and malvidin, and a malvidin derivative, along with the flavonol compounds, namely 3-O-glucoside and 3-O-glucuronide of quercetin, quercetin and kaempferol, were observed (Table 2). Total phenolic content of AP was 1000 mg kg À1 , consistent with values reported previously (Landl et al, 2010;Sun et al, 2015) and increased by 30% and 130% (to 1300 mg kg À1 and 2300) in AP-GS 3.0 and AP-GS 4.8, respectively. The amounts of soluble phenolics found in the fortified purees were exactly as expected based on the initial levels in apple and GS and on the addition, suggesting that these compounds were not strongly bounded to apple matrix.…”
Section: Formulation Of Apple Puree Fortified With Gssupporting
confidence: 90%